Moving Beyond Business as Usual Toward Regenerative Business Practice in Small and Medium-Sized Enterprises - Caldera, Savindi; Hayes, Samantha; Dawes, Les; Desha, Cheryl (Frontiers in Sustainability, 2022)
Environmental degradation is a complex global challenge requiring the urgent attention of small and medium-sized enterprises (SMEs), which are collectively responsible for a large proportion of global pollution. For those SMEs who are still thinking about sustainability at the level of the organisation and reducing its environmental damage, there must be an immediate shift in SME strategy and operations to consider planetary systems and practices that can regenerate ecosystems critical for the business’s success. Responding to this urgent need, the authors were keen to identify how SMEs could move from ‘doing less bad’ to ‘doing more good’, as a critically needed shift towards ‘regenerative business practice’. Using two case studies of Australian manufacturing sector SMEs already self-identified as regenerative business practices, their transition pathways and current operations were explored for insights and lesson learning that could be used to empower other SMEs. Collected interview data revealed three themes of priority during the two SMEs’ journeys: 1) Organisation and Nature conviviality; 2) Organisational freedom to innovate; and 3) Organisational innovative outlook. The SMEs’ experiences were also explored in relation to an ‘Action Framework for Regenerative Business’ developed by the authors. The framework draws on Stewardship Theory together with a set of ‘Principles and Strategies of Regenerative Business’ for SMEs to consider their current operations and identify opportunities for their next steps accordingly. Such directed actions are imperative to move away from just ‘reducing pollution’ to ‘restoring planetary systems’, demonstrating truly responsible consumption and production. Within the framework the authors add ‘advocate’ to the existing stewardship roles of ‘doers’, ‘donors’ and ‘practitioners’, which acknowledges the importance of this role in enabling SMEs to shift practices; in this case to regenerative business practice.